PENGARUH MODERNISASI SISTEM ADMINISTRASI PERPAJAKAN TERHADAP TINGKAT KEPATUHAN WAJIB PAJAK PADA KANTOR PELAYANAN PAJAK PRATAMA BATU - Sofiyana, Rindi Lestari Suci (Jurnal Mahasiswa Perpajakan, 2014)
This research is motivated because the tax administration system modernization efforts undertaken by the Directorate General of Taxation is the current omzet limit changes for the Taxable Enterprises inaugural from Rp 600.000.000,- to Rp 4,8 billion. with a change in that omzet limit, the number of Taxable Enterprises in Indonesia be on the wane. The purpose of this study to investigate the effect of variables modernization of tax administration on tax compliance partially and simultaneousl. This research used in quantitative research and the type of research is explanatory research. This study used a questionnaire as a means of collecting data with a sample of Taxable Enterprises were enrolled in the KPP Pratama Batu with sample method used nonprobability sampling by purposive sampling technique. Result of the research of t-test, it is known that changes in the organizational structure and the implementation of service significantly influence taxpayer compliance. While the development of information technology and the code of conduct employee has no effect and no significant effect on tax compliance. The results of the F test it is known that the independent variables consisting of changes in the organizational structure, implementation services, the development of information technology and the code of ethics of employees significantly affect the dependent variable is tax compliance. Keyword : Modernization, Taxpayer Compliance